PERMIAN AND TRIASSIC PALEOMAGNETISM OF THE SOUTHWESTERN TIEN SHAN: TIMING AND MODE OF TECTONIC ROTATIONS - Bazhenov M.L.; Chauvin A.; Audibert M.; Levashova N.M. (My University, 1993)
Volcanic rocks of the Lower Permian Luchob Formation and sedimentary rocks of the presumed Upper Permian Hanaka and Middle-Upper Triassic Madighen formations were studied in three localities in the southwestern Tien Shan. Primary magnetizations were isolated in Lower Permian and Triassic rocks, whereas the remanence of reversed polarity in the Hanaka Formation acquired during the Kiaman superchron may be slightly younger than the rock age. Inclinations in all three formations agree with the European reference data, but declinations are deflected westward. We argue that these deflections are due to the Late Permian-Late Triassic (but pre-Rhaetian) counterclockwise rotations and partly due to Late Cenozoic counterclockwise rotations. Inclinations in Permian and Lower Triassic rocks throughout the Tien Shan foldbelt, the Junggar basin and north Tarim are also in agreement with the reference data, implying that, within the error limits, this part of Central Asia was already welded together with Kazakhstan and the European plate in the Permian. Westward-deflected declinations throughout this region are accounted for not by movements of large blocks such as the Tarim but by domino-fashion Late Permian-Triassic rotations by strike-slip.
Keywords: Permian; Triassic; Палеозой::Пермская; Paleozoic::Permian; Мезозой::Триасовая; Mesozoic::Triassic